Interactive Visualization of Food Security Trends in North Aceh with a Business Intelligence Dashboard - Lidya Rosnita; Muhammad Ikhwani; Hafizh Al Kautsar Aidilof; Muhammad Muaz Munauwar (Brilliance: Research of Artificial Intelligence, 2025)
Food security in North Aceh Regency faces multifaceted challenges, including production fluctuations, price instability, and fragmented monitoring data across various institutions. These issues often hinder timely decision-making and the formulation of effective policies. Therefore, this study aims to develop a comprehensive Business Intelligence (BI) dashboard that can interactively visualize food security trends in North Aceh to support data-driven and evidence-based decision-making. The research methodology involves integrating data from multiple sources such as the Central Bureau of Statistics (BPS) and the Department of Agriculture using the ETL (Extract, Transform, Load) process to ensure consistency and accuracy. A data warehouse was then designed to store and manage the consolidated datasets efficiently, followed by the development of an interactive visual dashboard as the main analytical tool. The resulting dashboard is capable of visualizing six key parameters of food security through thematic maps, trend graphs, and comparative charts that allow users to observe temporal and spatial patterns. Advanced interactive features such as filtering, drill-down analysis, and cross-filtering provide users with the flexibility to independently explore data from different perspectives. The analysis demonstrates that the BI dashboard effectively integrates fragmented datasets, simplifies complex information, and enhances analytical capabilities for stakeholders. Overall, the findings indicate that implementing an interactive BI dashboard is a strategic and innovative solution to transform food security monitoring in North Aceh into a more proactive, integrated, and adaptive governance system, thereby strengthening regional resilience and policy responsiveness.